Analysis of jack-up units using a Constrained NewWave methodology - Cassidy, M; Taylor, R; Houlsby, G (2001)
There is a steadily increasing demand for the use of jack-up units in deeper water and harsher environments. Confidence in their use in these environments requires jack-up analysis techniques to reflect accurately the physical processes occurring. This paper is concerned with the models appropriate for the dynamic assessment of jack-ups, with a balanced approach taken in considering the non-linearities in the structure, foundations and wave loading. A work hardening plasticity model for spud-cans on sand is used for the foundation model. The spectral content of wave loading is considered using New Wave theory, and the importance of random wave histories shown by constraining the deterministic New Waves into a completely random background. A method for determining short-term extreme response statistics for a sea-state using Constrained New Waves is detailed. © 2001 Elsevier Science Ltd. All rights reserved.